2018
DOI: 10.1007/s12035-018-1365-5
|View full text |Cite
|
Sign up to set email alerts
|

Crybb2 Mutations Consistently Affect Schizophrenia Endophenotypes in Mice

Abstract: As part of the βγ-superfamily, βB2-crystallin (CRYBB2) is an ocular structural protein in the lens, and mutation of the corresponding gene can cause cataracts. CRYBB2 also is expressed in non-lens tissue such as the adult mouse brain and is associated with neuropsychiatric disorders such as schizophrenia. Nevertheless, the robustness of this association as well as how CRYBB2 may contribute to disease-relevant phenotypes is unknown. To add further clarity to this issue, we performed a comprehensive analysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 59 publications
(23 reference statements)
1
19
0
Order By: Relevance
“…Although sensorimotor gating alterations are typical symptoms in schizophrenia patients 47 and in patients with schizotypal personality disorder, which is believed to belong to the schizophrenia spectrum 48 , our findings reveal no schizophrenia-specific effects, but were found in the combined sample. The results converge with those observed in mice in which alterations of sensorimotor gating, measured as PPI, were the most consistent behavioral findings in the three homozygous mouse mutants 12 . PPI is largely regulated by neuronal connections between the limbic cortex (including the entorhinal cortex, hippocampus and amygdala), ventral striatum, ventral pallidum and the pontine tegmentum 49,50 .…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Although sensorimotor gating alterations are typical symptoms in schizophrenia patients 47 and in patients with schizotypal personality disorder, which is believed to belong to the schizophrenia spectrum 48 , our findings reveal no schizophrenia-specific effects, but were found in the combined sample. The results converge with those observed in mice in which alterations of sensorimotor gating, measured as PPI, were the most consistent behavioral findings in the three homozygous mouse mutants 12 . PPI is largely regulated by neuronal connections between the limbic cortex (including the entorhinal cortex, hippocampus and amygdala), ventral striatum, ventral pallidum and the pontine tegmentum 49,50 .…”
Section: Discussionsupporting
confidence: 89%
“…Compared to wildtype mice, O377 mutants displayed a decreased acoustic startle reflex (ASR) in combination with an increased prepulse inhibition (PPI). A recently published study confirmed alterations of sensorimotor gating (PPI) in both sexes in all 3 mouse mutant lines 12 . In addition, altered numbers of parvalbumin-positive interneurons were observed in the thalamic reticular nucleus (TRN) of these mice, which is consistent with results showing that a deficiency of parvalbumin, a calcium binding protein, is known to affect PPI 13 .…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…DCX+ and PV+ cell numbers were estimated in specific regions of interest (ROIs) with design-based stereology using the Stereo Investigator software system (StereoInvestigator, MBF Biosciences Inc.) on every sixth serial 40 µm coronal section with the Optical Fractionator probe as described previously 22,23 . The observer was blind to the experimental groups during analysis.…”
Section: Unbiased Stereological Estimates Of Dcx+ and Pv+ Cell Numbermentioning
confidence: 99%
“…These included the hippocampal dentate gyrus, Cornu Ammonis (CA) 1, 2/3 regions and the anterior cingulate cortex (ACC). We also quantified the PV+ cell number in the thalamic reticular nucleus (TRN) because of the dense PV+ cell population here and our previous evidence that it may play a role in NDD endophenotypes 23 . Volumetric analysis of selected ROIs was performed using the Cavalieri estimator probe as described previously 22 .…”
Section: Unbiased Stereological Estimates Of Dcx+ and Pv+ Cell Numbermentioning
confidence: 99%